2017
DOI: 10.1039/c7cc08252e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine catalysed (5 + 1) annulation of ynone/cinnamates with primary amines

Abstract: The (5 + 1) annulation of ynone/cinnamates and related substrates with protected primary amines gives rise to isoquinolones, pyrrolidinones and pyrrolopiperazines in good to excellent yields under phosphine catalysis. The reaction is viable with chiral phosphines, although the selectivity is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In 2017, Hooper, Lupton et al reported a [5 + 1] annulation of ynone/Michael acceptors with sulfonamides, affording isoquinolones, pyrrolidinones, and pyrrolopiperazines (Scheme 442). 516 Variations of the sulfonamide partner, the β -substituent of the ynone, the Michael acceptor, and the linker could be tolerated, with the desired products obtained in moderate to good yields and with good Z / E ratios. Nevertheless, use of an aliphatic linker and a pyrrole linker resulted in moderate yields.…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…In 2017, Hooper, Lupton et al reported a [5 + 1] annulation of ynone/Michael acceptors with sulfonamides, affording isoquinolones, pyrrolidinones, and pyrrolopiperazines (Scheme 442). 516 Variations of the sulfonamide partner, the β -substituent of the ynone, the Michael acceptor, and the linker could be tolerated, with the desired products obtained in moderate to good yields and with good Z / E ratios. Nevertheless, use of an aliphatic linker and a pyrrole linker resulted in moderate yields.…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…[2][3][4] While synthesis by stoichiometric generation of homoenolates has received attention for more than 50 years, [2] catalytic approaches have appeared more intermittently. [3,4] As part of ongoing studies on the umpolung of conjugate acceptors, [5,6] herein we report N-heterocyclic carbene (NHC) catalyzed [7] all-carbon (5+ +1) annulations by ah itherto unreported vinyl dianion synthon strategy.S pecifically, b-unsubstituted conjugate acceptors undergo homoenolate formation twice and couple to fivecarbon bis(electrophile)s to provide mono-and bicyclic cyclohexanones.T he reaction has been realized with inter-and intramolecular designs,a nd in some cases,w ith high levels of enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Alternately,iftwo of the three electrophiles are tethered then an intermolecular (5+ +1) reaction [Eq. (6)],i nvolving dimerization and cycloisomerization, should give cyclohexanones (i.e. 16).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] While synthesis via stoichiometric generation of homoenolates has received attention for more than 50-years, [2] catalytic approaches have appeared more intermittently. [3,4] As part of ongoing studies on the umpolung of conjugate acceptors, [5,6] herein we report NHC-catalyzed [7] all-carbon (5 + 1) annulations via a hitherto unreported vinyl dianion synthon strategy. Specifically, unsubstituted conjugate acceptors undergo homoenolate formation twice and couple to 5-carbon bis-electrophiles to provide mono and bicyclic cyclohexanones.…”
Section: Introductionmentioning
confidence: 99%